Gestare ferrum: Comparative Domain Modeling and Extrapolations of Iron Industries in the Qin-Han and Roman Mediterranean - 吴靖远 Ching-Yuan Wu (Dialogues d'histoire ancienne, 2025)
This paper addresses the methodological challenges of comparing the iron industries in the Qin-Han and Roman empires by creating "modeling domains" as a pragmatic and utilitarian approach. These domains, built from literary and archaeological evidence, represent generalized rules and frameworks, paired with diachronic, fragmented landscapes that depict the progressive acquisition and integration of lands with established metallurgical traditions. The paper argues that simply reaching this step is not enough, as each domain should be understood as part of a larger aggregative set, with an "external" dimension. The paper further discusses the distancing effect and the need for caution in cross-domain discussions, emphasizing the importance of historical and social specificity. The Roman-Parthian and Han-Nanyue examples are used to illustrate these challenges and opportunities. The paper concludes that the comparative approach should be ever-expanding, leading to a continual dialogue between domains and a deeper understanding of the dynamics of control, trade, and technological exchange in different historical and social contexts.